THE APPLICATION OF GOTHIC ARCHITECTURE ON SANTO LAURENSIUS CHIRCH ALAM SUTRA, SERPONG - Sisilia Hermawati ; C. Sudianto Aly ; Jonathan Hans Y. S (Riset Arsitektur (RISA), 2018)
Abstract- At a glance, the Church of Saint which Laurensius located in Serpong is like a church built in the past. However, when traced, it turns out this church is a new church that was built in 2007 by applying the Style of Gothic Architecture on the building. The application of elements of gothic architecture is not only visible from the outside of the church, but also on the inside of the church. For that, it will be further investigated about the application of any gothic elements contained in the study object.Gothic architectural elements are divided into several periods based on its development, ranging from Early Gothic, High Gothic, Late Gothic to Gothic Revival or Neo-Gothic. Gothic architectural elements have different characteristics and characters in each period of development. In this research, discussed theories about elements in gothic architecture based on its development. There are 17 elements analyzed in this research. These seventeen elements are summarized into three major sections covering the structural elements, non-structural elements, and spatial arrangements. Analysis of the application of gothic architectural elements to the Church of St. Laurensius begins by describing the elements present in the study object and then compared with the gothic architectural elements of the gothic period described in the second chapter. Based on the results of the analysis, it can be seen that from 17 elements observed, 12 elements of which are adapted from the building elements contained in the period of neo-gothic architecture.  Key Words: Gothic, Period, Element, Architecture, Neo-Gothic